Mass Scale Micropropagation Of Andrographis Paniculata (Burm. F.) Wall Ex Nees - Karim, MR; Bhadra, SK; Rahman, MM (Chittagong University Journal of Biological Sciences, 2024)
A reliable and efficient protocol was developed for in vitro propagation of Andrographis paniculata (Burm. f.) Wall ex Nees with the use of nodal and shoot tip explants. Nodal segments and shoot apex of in vitro grown seedlings were cultured on agar solidified MS medium supplemented with different concentrations and combinations of plant growth regulators (PGRs). Both the explants underwent direct organogenesis and produced multiple shoot buds. In case of shoot apex, maximum number of multiple shoot buds were formed when cultured on MS medium containing 1.5 mg/l Kn + 1.0 mg/l IAA. But nodal segments produced highest number of shoot buds on MS medium fortified with 1.5 mg/l BAP + 1.0 mg/l IAA. Multiple shoot buds underwent rapid elongation on elongation media and maximum elongation took place on MS medium fortified with 2.0 mg/l Kn + 1.5 mg/l IAA. Elongated shoot buds, on further culture in rooting media, produced strong and stout root systems. Half strength MS medium fortified with 2.0 mg/l IAA was most effective for induction and proliferation of roots. The healthy complete plantlets were successfully acclimatized and established in outside pots through successive phases of acclimatization. The Chittagong Univ. J. B. Sci.,Vol. 7(1 &2):121- 130, 2012.